The effect of water resources, natural vegetation and climate factors on the efficiency of road transport routes in Dhi Qar Governorate - METHAQ TALIB Khafaji ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2020)
The study dealt with water resources, climate and natural vegetation and their impact on the efficiency of the external land transport routes in the governorate, which numbered (18) roads, which showed that their impact is limited due to the technological development and their lengths reached (823.4 km) represented by the rapid, main and secondary traffic routes. Study (12,900 km2). The external land transport routes in the governorate have been linked to the neighboring governorates (Basra, Maysan, Qadisiyah, Muthanna, Wasit), as well as their link to the administrative units in the governorate, which number (20) administrative units, and the aim of the research is the impact of natural factors represented by water resources, climate and natural vegetation in Efficiency of external land transport routes in Dhi Qar Governorate, and the development of development plans to reduce the negative impact of these natural factors on the external road transport routes in the governorate, and the study reached a number of conclusions